Anxiety and depression versus treatment adherence among type II diabetes mellitus patients at government tertiary care institution, Madurai, Tamil Nadu - Swamynathan, Meenachi; Sivasubramanian, Priya (International Journal Of Community Medicine And Public Health, 2020)
Background: Global, Indian and Tamil Nadu prevalence of diabetes mellitus (DM) was 8.5%, 7.7% and 10.4% respectively. Prevalence of anxiety or depression was higher among diabetics in comparison to general population. Treatment adherence was related to prevention of mortality and morbidity. Currently anxiety or depression are not looked for and data is scarce regarding the burden of anxiety or depression among type II DM patients. The objectives of the study were to estimate proportion(s) of type II diabetes patients having anxiety or depression; having treatment adherence and to determine the association between anxiety or depression and treatment non adherence. Methods: We did cross sectional study among type II DM patients at Government Rajaji Hospital, Madurai and did consecutive sampling. The sample size of the study was 96 which was collected diet and exercise details. It used Morisky medication adherence questionnaire and hospital anxiety and depression scale to measure medication adherence and anxiety and depression. The study was calculated proportions and odds ratio with confidence intervals, obtained Ethics clearance and referred participants who had anxiety or depression to Psychiatrist. Results: Proportion of anxiety or depression was 36.5% (27.3 to 46.4). 55% had adequate diet adherence, 48% had adequate exercise adherence, 68% had adequate medication adherence, 40% (29.8 to 50.1) had adherence to all the three. Odds of anxiety or depression among poor treatment adherents was 4.1 (1.6 to 11.4) times more in comparison to their counterparts. Conclusions: Proportions of anxiety or depression and treatment adherence were 37% and 40% among diabetics. Anxiety or depression could be a potential risk factor for poor treatment adherence. We recommended screening for anxiety and depression in the follow up of diabetics.